A study of Craniospinal Imaging in Patients with Anorectal Malformation - Chanchlani, Roshan; Agravat, Mehul; Agarwal, Vikesh; Agarwal, Rekha; Rathore, Sunil (International Journal of Medical Research and Review, 2014)
Introduction: Anorectal malformations are commonly associated with craniospinal abnormalities like hydrocephalus, tethered cord syndrome, occult spinal dysraphism, syringomyelia, meningomyelocele and Arnold Chiari malformation. Aim of our study was to identify the incidence of craniospinal anomalies in patients with anorectal malformation and to analyse utility of Ultrasound and MRI as a screening tool in these patients to detect such anomalies. Material and Method: 52 infants male and female of anorectal malformation were included. All underwent ultrasonography of brain and spinal cord and 27 patients underwent MRI to detect craniospinal anomalies. Result: Out of 52 cases 38(73.07 %) were males and 14(26.93 %) were females. High type ARM (34.61 %) and Vestibular fistulas(19.23 %) were most common type in male & female child respectively. On ultrasonography in this series no craniospinal abnormality was found. On ultrasonography subarachnoid space was normal in all cases and central canal diameter was found <1cm in all cases. No abnormalities were detected in posterior fossa like cistermagna dilatation, dilated ventricles, Chiari Malformation. MRI spine was done 27 patients with high and low type malformation, but no abnormality was detected. Conclusion: Craniospinal anomaly and tethered cord are not frequently found in patients with anorectal malformation, in Northern Indian Population. As no association was found between craniospinal anomalies and anorectal malformation in the present study, the use of Ultrasonography and MRI as a screening tool is not recommended unless clinically indicated.